The Role of Stevia in Diabetes Management: A Research Overview (International Journal of Scientific Research in Science and Technology, 2025)
Diabetes mellitus, a chronic metabolic disorder characterized by hyperglycemia, poses significant health challenges globally. Managing blood glucose levels is crucial for diabetic patients to prevent complications. Stevia rebaudiana, a natural sweetener derived from the Stevia plant, has been investigated for its potential role in diabetes management due to its non-caloric and low glycemic properties. This paper reviews the current evidence on the impact of stevia on diabetes, focusing on its effects on glycemic control, insulin sensitivity, and overall metabolic health.